2009
DOI: 10.1002/lary.20602
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte growth factor protects auditory hair cells from aminoglycosides

Abstract: These findings demonstrate that a functional HGF/c-Met coupling is present in the cochlea, and HGF application exerts protective effects on hair cells, indicating the potential of HGF as a therapeutic agent for sensorineural hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
3
14
2
Order By: Relevance
“…However, these insults cannot be applied to the explant culture system. Therefore, we used aminoglycoside (neomycin), which is commonly used in this type of study (Kikkawa et al, 2009;Yoshida et al, 2011) to injure hair cells of cochlear explants. The administration of 100 ng/ml of IGF-1 markedly protected both the inner and outer hair cells (IHCs and OHCs) from neomycin injury ( Figure 1A and B).…”
Section: Igf-1 Protects Cochlear Hair Cells Against Neomycinmentioning
confidence: 99%
“…However, these insults cannot be applied to the explant culture system. Therefore, we used aminoglycoside (neomycin), which is commonly used in this type of study (Kikkawa et al, 2009;Yoshida et al, 2011) to injure hair cells of cochlear explants. The administration of 100 ng/ml of IGF-1 markedly protected both the inner and outer hair cells (IHCs and OHCs) from neomycin injury ( Figure 1A and B).…”
Section: Igf-1 Protects Cochlear Hair Cells Against Neomycinmentioning
confidence: 99%
“…S4F). Several studies of inner ear disease have reported that HGF protects hair cells and improves hearing (25)(26)(27). However, HGF levels appear to be tightly regulated, as too much or too little HGF is associated with hearing loss (28).…”
Section: Resultsmentioning
confidence: 99%
“…Genetic studies of hundreds of genes necessary for audition have uncovered several pathways important for normal hearing. Based initially upon studies of animal model, growth factors are now being explored for treatment of noise and ototoxic induced deafness and age-related hearing loss, [100][101][102][103][104][105][106][107][108][109] and some of these are currently in clinical trials. 110,111 For example, topical application of IGF1 to the middle ear was used to treat sudden sensorineural hearing loss in humans, and some treated individuals showed improvements of 10 to 30 dB for tested frequencies as compared to controls.…”
Section: Discussionmentioning
confidence: 99%